Electronic processes in non-crystalline materials - Mott, N. F. (Nevill Francis), Sir, 1905-1996 (International series of monographs on physics (Oxford, England), 2012)
Since the first edition of this highly successful book the field saw many great developments both in experimental and theoretical studies of electrical properties of non-crystalline solids. It became necessary to rewrite nearly the whole book, while the aims of the second edition remained the same: to set out the theoretical concepts, to test them by comparison with experiment for a wide variety of phenomena, and to apply them to non-crystalline materials. Sir Nevill Mott shared the1977 Nobel Prize for Physics, awarded for his research work in this field. The reissue of this book as part of th.